If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2 = 6x + 18 Reorder the terms: -2 + x = 6x + 18 Reorder the terms: -2 + x = 18 + 6x Solving -2 + x = 18 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -2 + x + -6x = 18 + 6x + -6x Combine like terms: x + -6x = -5x -2 + -5x = 18 + 6x + -6x Combine like terms: 6x + -6x = 0 -2 + -5x = 18 + 0 -2 + -5x = 18 Add '2' to each side of the equation. -2 + 2 + -5x = 18 + 2 Combine like terms: -2 + 2 = 0 0 + -5x = 18 + 2 -5x = 18 + 2 Combine like terms: 18 + 2 = 20 -5x = 20 Divide each side by '-5'. x = -4 Simplifying x = -4
| 1/2x-3/4=3/8 | | (5+x)-6=7 | | 2(10*2)=30+10 | | 3x-44=56-2x | | x/12-15=36 | | -3n=-5 | | 40=3/4x-32 | | 2(10*10)=30+10 | | 21-3=18 | | 21x+7=3x+1621-3 | | 2x/8-3/4=5/12 | | 5+8m=7m+2 | | -9a-3=-36 | | 5-8x=16-8 | | 1+(6)(8)= | | N-7=-3+2n | | 39x+33=501 | | 2x-3=2x+10 | | (1/5)^2x=125 | | 2x+2y=990 | | 8/19 | | 5(4+r)=.5(40+10r) | | M+3=9+3m | | w=m+6 | | 4x-9+17=3x+5 | | w=5m-10 | | 4(2)(2)= | | -4(6x-3)= | | 6=2/3x-6 | | 6x+25=16-3x | | 27-10x=7 | | (X-4)(x+9)=(x+5)(x-3) |